The Nature of Need Structure in Nonwork - Jamal, Muhammad; Baba, Vishwanath; Mitchell, Vance (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1982)
This study attempts to verify the appropriateness of three existing taxonomies of need fulfillment by Maslow, Alderfer and lawler, respectively, in the area of nonwork.